2022
DOI: 10.1186/s12905-022-01715-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between reproductive history and menopausal symptoms: an evidence from the cross-sectional survey

Abstract: Background During menopause, women experience annoying symptoms which may affect their daily activities and quality of life. This study aimed to determine whether reproductive history, an important indicator of estrogen exposure across the lifetime, is associated with the severity of menopausal symptoms in women. Methods This study was a cross-sectional study conducted on 214 women aged 35–65 who were randomly selected, and data was collected by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There has been much academic research on the impact of fertility on the health of mothers, but the conclusions are not consistent. Some studies have reported a negative impact of fertility on maternal health, while others have observed a non-linear or positive relationship between the two variables [3][4][5][6][7][8][24][25][26]. Most research has focused on the health of older mothers, with limited attention given to how fertility influences the health The finding suggests that there is a significant negative correlation between the number of children born and the self-rated health of migrant women of childbearing age; in addition, an elevation in the socioeconomic status can act as a positive moderator and mitigate the negative impact of fertility on the health of migrant women.…”
Section: Discussionmentioning
confidence: 99%
“…There has been much academic research on the impact of fertility on the health of mothers, but the conclusions are not consistent. Some studies have reported a negative impact of fertility on maternal health, while others have observed a non-linear or positive relationship between the two variables [3][4][5][6][7][8][24][25][26]. Most research has focused on the health of older mothers, with limited attention given to how fertility influences the health The finding suggests that there is a significant negative correlation between the number of children born and the self-rated health of migrant women of childbearing age; in addition, an elevation in the socioeconomic status can act as a positive moderator and mitigate the negative impact of fertility on the health of migrant women.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found no significant correlation between age, marital status, career, the number of children, and menstruation regulation and the occurrence of menopausal symptoms through univariate analyses, which differed from the results of studies in other countries. A Turkish study noted that women with a menopausal age of 44–50 years had a higher risk of developing menopausal symptoms [ 30 ]; a survey among women in the community showed that marital status was one of the factors affecting menopausal symptoms [ 31 ]; the results of a Greek study showed that women who were employed had less severe menopausal symptoms [ 32 ]; an Iranian study noted that women with a high number of children had more severe menopausal somatic symptoms [ 33 ]; and a Sri Lankan study noted that postmenopausal women had more severe menopausal symptoms than premenopausal women [ 34 ]. The differences between the results of the foreign studies and the results of the present survey may be due to differences in national policies and the demographic characteristics of the respondents; for example, the one-child policy was implemented in 1979 in China [ 35 ], so 76% of the women in the present survey had only one child; in addition, 95% of the respondents in the present study were married, which lacked comparability.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al also found that age at rst childbirth, the childbearing period and the number of children born signi cantly increased parental depression [12]. The study by Sharami et al found that women with a higher number of children were more likely to have higher total and somatic symptoms than others [13].…”
Section: Theories and Literature Reviewmentioning
confidence: 97%